Farmers’ decisions in agricultural systems in relation to seasonal rainfall variability, in semi-arid environments in Morocco, the case of the region of Abda - Bassir, Assmaa; El- Assaad, Mohammed (Journal of agricultural, environmental and veterinary sciences, 2019)
This study aims at investigating farmers’ decisions in agricultural systems and their relation to seasonal rain change in the semi-dry environments in Morocco, the case of Abda region. The research attempts to answer the following problematic question: How does seasonal rain change affect peasant decisions in agricultural systems, in semi-dry environments in Morocco, the case of the same region? The research target is to achieve the following objectives: First: Description of the farmers’ decisions in agricultural systems in the semi-dry environments in Morocco, the case of the same region, second: the interpretation of the relationship of the farmers’ decisions in agricultural systems represent the seasonal rain change the case of the same region. To answer the problematic question, we have adopted the following statistical hypothesis: There are no statistically significant differences (H0) in peasant decisions in agricultural systems by representing the seasonal rain change in semi-dry environments in Morocco, the case of the same region. The research was based on two methods of data collection: one on documents and archives, and the other on the observation of terrain based on the sample and the questionnaire, which included the interrogation of 238 farmers taken from a real sample of 465 farmers during the year 2016. The research also adopted a method of data processing based on descriptive and indicative statistics. In addition, it also adopted the «IMRAD» method, which has the following four scientific qualities: Introduction (I) .Methodology (M), Results (R) and Discussion (D).